Impact of COVID-19 on Mental Health of Dhaka University Students (Dhaka University Journal of Biological Sciences, 2023)
Student mental health in the university setting has been an expanding concern. The COVID-19 pandemic could be detrimental to the psychological wellness of university students. The aim of this investigation was to see the mental health outcomes of Dhaka University students during the COVID-19 outbreak. A crosssectional survey using a convenient sampling technique was conducted among 193 students of the University of Dhaka within a time duration of 1 month. Data was gathered by utilizing the web survey including DASS-21BV, demographic questions, and health-related queries with respect to COVID-19. The prevalence of anxiety symptoms and depressive symptoms was 64.2 % and 66.9%, respectively, and 51.8% of students reported mild to extremely severe levels of stress. Age group was significantly associated with DASS-21 depression subscale scores (χ2 (2)> =14.179, p= .007). Hall status was also significantly associated with DASS-21 anxiety subscale scores (χ2 (2)> =10.001, p= .040). Sleep-related queries with respect to COVID-19 were significantly associated with DASS-21 anxiety subscale scores (χ2 (2)> =24.135, p= .002). COVID-19-related queries on attention, enthusiasm, mental state, and self-confidencewere also significantly associated with depressive symptoms, anxiety symptoms, and stress levels (p